Model Bimbingan Konseling Berbasis Religiusitas dalam Mengatasi Kesulitan Belajar Siswa - Siti Bahiroh; Fitriah M. Suud (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to explore guidance based on religious counseling, namely through internalization of Islamic values in private schools in Yogyakarta. This qualitative research uses a case study approach. Data collection by observation, interview, and documentation. Participants were 7 counseling guidance teachers, Principal, deputy headmaster, 8 teachers. The results showed that students' problems appeared related to discipline, morals, learning and discipline. The cause is more influenced by the use of gadgets and environmental influences. The religiosity-based counseling model that is applied is to invite students to enter the mosque, to make good habits, to set an example, to help students to be comfortable in learning and to share with students when they are relaxed.